Jabatan Kepala Desa dalam Rijksblad Van Surakarta Tahun 1931 Nomor 9 - Riza Multazam Luthfy; Achmad Safiudin R. (Fakultas Hukum Universitas Islam Malang, 2026)
Historical legal studies employing historical analysis, as well as historical research utilizing legal perspectives, have received relatively limited attention in Indonesia. Therefore, strengthening legal history studies, particularly those concerning rijksblad, is necessary. This research aims to examine the regulation of Village Heads in Rijksblad van Surakarta 1931 Number 9 from a legal-historical perspective. The study applies a normative legal method using statutory and historical approaches. The findings reveal two principal conclusions. First, the regulation positioned Village Heads primarily as state administrative officials rather than representatives of village communities. Their main functions included administering tax collection and allocating labor obligations for state purposes. Second, Village Heads were exempted from compulsory state labor, indicating their relatively privileged status within the colonial administrative structure. Based on the perspective of legal history, these provisions demonstrate a transformation in the position of Village Heads from local customary leaders into administrative agents supporting colonial administration functions.